2017
DOI: 10.1039/c6nj03795j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of avermectin microcapsules with anti-photodegradation and slow-release by the assembly of lignin derivatives

Abstract: A facile, environmentally friendly, and low-cost strategy for affording stability and the slow-release of avermectin based on self-assembly of lignin derivatives is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Polyphenols have exhibited good resistance to UV radiation and to photothermal effects [46], and, for these reasons, are typically used as sunscreens in various cosmetics. Prior work has also demonstrated that the encapsulation of Av is an effective way to improve photostability [15,47]. In the present work, the formation of TA/Fe 3+ films on the Av particles was predicted to partly shield these granules from UV light, and this is confirmed by the photodegradation results presented in Figure 4.…”
Section: The Photodegradation Of Avermectin Wdg Formulationssupporting
confidence: 73%
“…Polyphenols have exhibited good resistance to UV radiation and to photothermal effects [46], and, for these reasons, are typically used as sunscreens in various cosmetics. Prior work has also demonstrated that the encapsulation of Av is an effective way to improve photostability [15,47]. In the present work, the formation of TA/Fe 3+ films on the Av particles was predicted to partly shield these granules from UV light, and this is confirmed by the photodegradation results presented in Figure 4.…”
Section: The Photodegradation Of Avermectin Wdg Formulationssupporting
confidence: 73%
“…70 Thus far, the particles have been used for entrapment and adsorption of many different active substances, as reviewed, 17 and their release properties have provided indirect information of the packing and porosity of the particles. 9,10,72,73 In general, the accumulated results indicate that LNPs from the solvent-exchange method are penetrable to water, which explains a rather rapid release of water-soluble small molecules, 9,10 while bulkier compounds are released at lower rates. 72,73…”
Section: Dry Particlesmentioning
confidence: 99%
“…As could be expected from this mechanism, most of the substances entrapped in LNPs are low‐molecular‐weight compounds with low water solubility (Figure ). Pesticides (herbicides, insecticides, microbicides) constitute the largest class of compounds that were entrapped. Commercial interest in lignin‐based carriers is at least partly due to the well‐suited intrinsic properties of lignin as a polyphenol.…”
Section: Entrapment Encapsulation and Adsorption Of Active Substancmentioning
confidence: 99%
“…Entrapment efficiencies (EE [%]) were reported to vary broadly from 4 % to >95 % depending on the carrier formation process, the lignin carrier morphology, and the type of entrapped active ingredient (Table ). Typical loading capacities (LC) were less than 20 wt %, with a few exceptions of higher concentrations . However, methods used to analyze the LC and EE have not been standardized for lignin particles.…”
Section: Entrapment Encapsulation and Adsorption Of Active Substancmentioning
confidence: 99%
See 1 more Smart Citation